Vapour application of sage essential oil maintain tomato fruit quality in breaker and red ripening stages - Chrysargyris, Antonios; Rousos, Charalampos; Xylia, Panayiota; Tzortzakis, Nikos G. (My University, 2021)
Consumers seek safe, high-nutritional-value products, and therefore maintaining fresh produce quality is a fundamental goal in the food industry. In an effort to eliminate chemical-based sanitizing agents, there has been a shift in recent decades toward the usage of eco-friendly, natural solutions (e.g., essential oils-EOs). In the present study, tomato fruits (Solanum lycopersicum L. cv. Dafni) at breaker and red ripening stage were exposed to sage essential oils (EO: 50 μL L−1 or 500 μL L−1) for 2, 7 and 14 days, at 11 °C and 90% relative humidity (RH). Quality-related attributes were examined during (sustain effect-SE) and following (vapour-induced memory effect-ME; seven days vapours + seven days storage) vapour treatment. In breaker tomatoes, EO-enrichment (sustained effect) retained fruit firmness, respiration rates, and ethylene emission in low EO levels (50 μL L−1). In contrast, breaker fruit metabolism sped up in high EO levels of 500 μL L−1, with decreased firmness, increased rates of respiration and ethylene, and effects on antioxidant metabolism. The effects were more pronounced during the storage period of 14 days, comparing to the fruit exposed to common storage-transit practice. In red fruits, the EOs impacts were evidenced earlier (at two and seven days of storage) with increased rates of respiration and ethylene, increased β-carotene, and decreased lycopene content. In both breaker and red ripening fruit, EO application decreased weight losses. Considering the fruits pre-exposed to EOs, quality attributes were more affected in green fruits and affected to a lesser level in the red ones. Furthermore, based on appearance, color, and texture evaluations, organoleptic trials demonstrated an overwhelming preference for EO-treated red fruit during choice tests. EOs had lower effects on total phenolics, acidity, total soluble solids, and fruit chroma, with no specific trend for both breaker and red tomatoes. Natural volatiles may aid to retain fruit quality in parallel with their antimicrobial protection offered during storage and transportation of fresh produce. These effects may persist after the EO is removed from the storage conditions.
Keywords: Fruit storage; Natural products; Quality-related attributes; Tomato; Volatiles